A comparison of male and female renal pelvis urobiome of unilateral stone formers using 2bRAD-M - Hong, Sen-Yuan; Miao, Lin-Tao; Yang, Yuan-Yuan; Wang, Shao-Gang (BMC microbiology, 2024)
Urolithiasis is a prevalent urological ailment characterized by increasing prevalence and recurrence rates, resulting in substantial social and economic burden. While men exhibit an incidence rate nearly twice that of women, this gender disparity is gradually diminishing. Nevertheless, the mechanisms underlying this condition remain incompletely elucidated. The identification of the urinary microbiome (urobiome) has provided a fresh perspective on urolithiasis. This study aimed to analyze the urobiome of unilateral stone formers in the renal pelvis and evaluate the variations in microbial diversity and community composition between males and females. Renal pelvis urine samples were obtained from a cohort of 21 male and 9 female patients and subsequently subjected to taxonomic and functional analysis using 2bRAD sequencing for Microbiome (2bRAD-M). The collected samples were categorized into four distinct groups, namely the stone side of males (SM), stone side of females (SF), non-stone side of males (NSM), and non-stone side of females (NSF). Through the application of beta diversity analysis, dissimilarity was observed between NSM and NSF. Additionally, NSF exhibited a higher abundance of microbial populations, and a total of 29 distinct species were identified as differentially present between NSM and NSF using LEfSe. Lactobacillus iners, Atopobium deltae, Lawsonella clevelandensis, and Meyerozyma guilliermondii exhibited enrichment in the SF group compared to the SM group. Furthermore, we identified distinct species that differed between the SM and NSM groups, as well as the SF and NSF groups. Besides, we conducted COG annotation and KEGG pathway predictions, revealing significant differences in urobiome function across the different groups. Variations in microbial community composition and predicted functions were observed among the various groups. Future research could potentially leverage the urobiome to personalize urolithiasis treatment based on individual microbial characteristics, taking into account gender-specific differences.